Research on the cutting dynamics for face-milling of spiral bevel gears. (15th May 2021) - Zheng, Fangyan; Han, Xinghui; Lin, Hua; Zhao, Wanhua
Graphical abstract: Highlights: Proposes an analytical dynamic model of face-milling for spiral bevel gear. Investigates the un-deformed chip geometry and static cutting force for spiral bevel gear. Discusses the dynamic equation and semi-discretization method for chatter stability analysis. Validates the proposed model through the simulation and experiment. Abstract: For an efficient and precise machining of spiral gear, the special face-milling process for spiral bevel gear is developed and widely used, exhibiting great difference from the general milling process in cutting machine, cutter and cutting kinematics. The un-deformed chip geometry, cutting force model and regenerating mechanism are hence complexly different, bringing great challenge to the modeling of cutting dynamics. In this regard, no relevant work can be found at present. To overcome this problem, through fully investigating the cutting force regenerating mechanism under complicated cutting kinematics, this paper first develops an analytical cutting force prediction model by classifying the chip geometry into 6 cases, and then a simplified dynamic chip model by assuming the chip geometry cases unchanged and ignoring edge alteration. On such basis, the model for prediction of the cutting dynamics and the chatter stability are developed and validated. Besides, the 3D stability lobe for face-milling of spiral bevel gear is presented and the cutting system tends to be stable with high cutter gear ratio and cutting speed.